Information Providing in COVID-19 by Health Professionals in Pakistan - Muhammad Shahjahan, Misbah Jabeen, Ghulam Farid, (Pakistan Journal of Medical & Health Sciences, 2022)
Purpose: This study analyses the impact on postgraduate students' educational activity at an Allied Health Sciences institute in Pakistan as well as the information distribution during the Covid-19 pandemic. Methodology: The current quantitative analysis is based on a survey that was conducted among postgraduate allied health science students in various universities in Lahore, Pakistan, to evaluate the efficacy of information distribution during the Covid-19 pandemic. Finding: The response rate of the study remained 80%. Majority of users, Approximately 69.5% (n=66) of students said they had no trouble getting information during COVID-19, whereas 30.5% (n=29) of students said the information was subpar. Respondents of the study found highly satisfied with the efficiency of library on providing e-services during Covid-19 (P-Value = 0.487). usability of libraries in information dissemination which 74 (78%) respondents said that libraries offer access to trustworthy and reliable Covid-19 pandemic information through a variety of media There is consensus among 75 (or 79%) of the students on the importance of raising awareness and educating people on how to contain the Covid-19 outbreak, as well as the difficulties libraries face in disseminating information. 77 (81%) students said they lack the knowledge and abilities necessary to effectively use the tools and services available on the Internet. The recommendations of the study might be beneficial to enhance the effectiveness of resources and services of universities libraries. Keywords: University Library; Library Website; Library User; Covid-19 Pandemic; Information Dissemination; Information Technology; Post Graduate Allied Health Science, Students.